Utilização de metodologias de gestão de risco na implementação de um Sistema integrado de gestão (ERP): estudo de caso em uma empresa industrial de grande porte - Araujo, Renato Gomes de (2013)
The usage of Entrerprise Resource Planning (ERP) systems in companies has become increasingly common. Its implementation, in turn, brings risk factors which require management. The aim of this study was to analyze the risk management practices adopted on an ERP implementation in a Brazilian subsidiary of a large industrial company, comparing them to the risk management model described in PMBOK PMI, investigating the reasons why such a model was adopted or not and the reasons, if applicable, in adopting practices not described in this model. The difficulties to manage project risk were examined, to identify and link its causes. A qualitative study was prepared based analysis of interviews and other documents like meeting minutes, emails, spreadsheets and communications. This research evidences there was the identification of project risks and the development of an action plan to eliminate or mitigate them, but its scope was limited by some problems of organizational, technical and behavioral nature existing in the company.